2007
DOI: 10.1111/j.1744-6163.2007.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Nursing Intervention for Voice Hearing

Abstract: These findings provide encouragement for nurses to further develop and investigate cognitive strategies to treat psychiatric symptoms of voice hearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…, Poole & Grant , Turkington et al . , England ). Mullen () reviewed the literature on psychological interventions in acute care mental health units and found that while research evidence supports the use of psychological interventions, they were not being used by MHNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Poole & Grant , Turkington et al . , England ). Mullen () reviewed the literature on psychological interventions in acute care mental health units and found that while research evidence supports the use of psychological interventions, they were not being used by MHNs.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that when MHNs incorporate CBT into their nursing practice, long‐term improvements in health outcomes occur (Chan & Leung , Department of Health , Poole & Grant , Turkington et al . , England ). Turkington et al .…”
Section: Introductionmentioning
confidence: 99%
“…2003, Simon et al. 2006, England 2007). In contrast, the term ‘nurses’ was used without detailed information about their experiential backgrounds in attending to the needs of patients presenting with a psychiatric issues (Hunkeler et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the reviewed evidence measured by the BPRS, two of the three studies found significant pre‐ and post‐test differences. When England (2007) evaluated a cognitive nursing intervention, 44 persons diagnosed with schizophrenic spectrum disorders had greater improvement in their symptoms than did the 21 persons in the control group at 1 year. Rabins et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation